1989
DOI: 10.1149/1.2096455
|View full text |Cite
|
Sign up to set email alerts
|

Application of Videomicroscopy to In Situ Studies of Electrodeposition

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…She combined a long-range microscope objective on a traveling stage with a video camera/cassette-recorder to record the growth of zinc nodules. The resolution achieved was about 1 I.tm [31]. McVay showed that nodules coalesce and elongate both downstream and upstream, though predominantly in the former direction [30].…”
Section: Striated Zinc Electrodepositsmentioning
confidence: 97%
See 4 more Smart Citations
“…She combined a long-range microscope objective on a traveling stage with a video camera/cassette-recorder to record the growth of zinc nodules. The resolution achieved was about 1 I.tm [31]. McVay showed that nodules coalesce and elongate both downstream and upstream, though predominantly in the former direction [30].…”
Section: Striated Zinc Electrodepositsmentioning
confidence: 97%
“…When the nodules reach a critical size, approximately 20 um in height, they begin to elongate in the direction of flow, as shown by McVay [31] and Jaksic [22][23][24].…”
Section: Stages Of Zinc-deposit Morphological Developmentmentioning
confidence: 99%
See 3 more Smart Citations